SPEECH ACTS IN THE MAIN CHARACTER’S DIALOGUE ON SYDNEY WHITE MOVIE - Sumarni Parapat and Muhammad Natsir (LINGUISTICA, 2015)
This study deals with Speech Acts used in Sydney White movie’s dialogue. Thepurpose of this study was to find out the types of speech acts based on GeorgeYule’s theory and to find out which types were dominant in the dialogue.Character that to be analyzed was Sydney White’s utterance. Sydney White wasthe main character in “Sydney White” movie. The research was conducted byusing descriptive qualitative approach. There were five types of speech acts inSydney White movie script. They were 7 Declarations (1.97%), 120Representatives (33.89%), 93 Expressives (26.27%), 125 Directives (35.33%),and 9 Commisives with the total percentage of 2.54%. The findings of this studyshowed that Directives was the dominantly used in this movie. There were 125(35.33%) utterances that uttered by the main character namely Sydney White in“Sydney White” movie. Directive was the dominantly used in the moviebecause Directives uttered when the main character intends to give commands,orders, requests, suggestion, warning, permitting, urging, questioning, advising,begging, challenging.